Mitochondrial DNA copy number in autism spectrum disorder and attention deficit hyperactivity disorder: a systematic review and meta-analysis - Al-Kafaji, Ghada; Jahrami, Haitham Ali; Alwehaidah, Materah Salem; Alshammari, Yasmeen; Husni, Mariwan (Frontiers in Psychiatry, 2023)
Background: Several reports suggest that altered mitochondrial DNA copy number (mtDNA-cn), a common biomarker for aberrant mitochondrial function, is implicated in autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD), but the results are still elusive. Methods: We conducted a meta-analysis to summarize the current evidence and to provide a more precise assessment of the mtDNA-cn in ASD and ADHD. We searched the MEDLINE-PubMed, Scopus, and EMBASE databases to identify relevant studies up to the end of February 2023. The meta-analysis was conducted according to the predetermined protocol following the recommendations of the Cochrane Handbook of Systematic Reviews. Results: Fourteen studies involving 666 cases with ASD and ADHD and 585 controls were collected and judged relevant for the systematic review and meta-analysis. The results were pooled by a random effects meta-analysis and the findings were reported as a geometric mean of the estimated average response ratio and 95% confidence interval. Overall analysis of all studies reported differences in the mtDNA-cn in blood samples (n=10) and non-blood samples (brain tissues and oral samples; n=4) suggested a significant increase in the mtDNA-cn in patients than in controls (P = 0.0275). Subgroup analyses, by stratifying studies based on tissue type, showed no significant increase in mtDNA-cn in the blood samples between patients and controls (P = 0.284). Conversely, a significant increase in mtDNA-cn was observed in the non-blood samples in patients than in controls (P = 0.0122). Further stratified analysis by blood cell compositions as potential confounds showed no significant difference mtDNA-cn in peripheral blood samples of patients comparted to controls (P = 0.074). Conclusion: In this first meta-analysis of the evaluation of mtDNA-cn in ASD/ADHD, our results show elevated mtDNA-cn in ASD and ADHD, further emphasizing the implication of mitochondrial dysfunction in neurodevelopmental disorders. However, our results indicate that the mtDNA-cn in blood is not reflected in other tissues in ASD/ADHD, and the true relationship between mtDNA-cn measured in blood samples remains to be defined in future studies. The potential of mtDNA-cn as a biomarker for mitochondrial malfunction in neurodevelopmental disorders deserves further investigations.